Review on viability and implementation of residential PV-battery systems: Considering the case of Dominican Republic - Edwin Garabitos Lara (Elsevier, 2021)
The reduction in the costs of residential photovoltaic (PV) systems has increased their viability and implementation for self-consumption and export of energy electricity. The implementation of these systems requires feasibility studies, considering the structure of the electricity tariff, the stability in the grid, the incentives and other variables. This work reviews 158 papers on the viability and sizing of residential PV systems, with the purpose of showing a general overview of the subject and that serves as a guide to carry out future research in the residential sector. The results show that the simulation methodology is the most frequent in the techno-economic study of residential PV systems, with a percentage of 45% followed by optimization with 37%; 29 analysis tools were identified in the study of residential PV systems, being MATLAB the most used . The combination of PV systems with batteries or Battery Energy Store System (BESS) has been increasing in the literature, even over PV systems without batteries. In addition, the case of the Dominican Republic is analyzed, identifying three cases to be evaluated, considering the Net metering (NM) program, self-consumption, step tariff and electricity outages. It was determined that in the Dominican Republic, the installed residential PV systems capacity in NM program is approximately 7.83 kW/user .